The Influence of Ethnoscience-Based Learning Video to Improve Students’ Understanding of Green Chemistry in Integrated Science Subject - Adhi, Danang Triasmoro; Sudarmin, Sudarmin; Linuwih, Suharto (Journal of Innovative Science Education, 2018)
Indonesia is a country with a lot of culture and wisdoms. These identities are proudly upheld and maintained by every citizens of the nation. Education plays an important role in preserving these values, including to insert it into classroom activities. Ethnoscience-based learning process is hoped to change teacher-centered learning stigma to a contextual and meaningful learning. This research aims to develop learning video for integrated natural science class with ethnoscience basis and implementation of green chemistry principle for students. The used method in this research was research and development with a 4D modification. The result were obtained from the judgment of experts of media, materials, and ethnoscience. The judgment proved that the media was very properly able to be used. The responses of the teachers and students to the video was very good. The effectiveness of the video was shown with n-gain value of 0.52 or the criterion of medium. Based on the research, it can be concluded that the use of video were very proper to develop students’ understanding of green chemistry based on the National Education Standardization Agency.